1995
DOI: 10.1080/00288233.1995.9513146
|View full text |Cite
|
Sign up to set email alerts
|

The role of shelterbelts in protecting livestock: A review

Abstract: Planting a shelterbelt is the only option open to some New Zealand livestock farmers for reducing the adverse effects of wind. Wind reduces pasture productivity by mechanically agitating the leaves and this results in inhibition of plant cell expansion. It causes greater evaporation and physical damage to the plants, which also reduce pasture yield. At any given temperature, wind raises the lower critical temperature for an animal, and this is potentially wasteful in terms of energy utilisation, and it increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 94 publications
2
64
0
1
Order By: Relevance
“…Usually it is recommended that wind-permeable barriers such as windbreak material or trees are used for stock shelter, because solid barriers create turbulence on the leeward side (Gregory 1995). However, ewes and lambs prefer barriers with low wind permeability (Winfield et al 1969;Lynch & Alexander 1977;Alexander et al 1979;.…”
Section: Effective Design and Location Of Sheltermentioning
confidence: 99%
See 1 more Smart Citation
“…Usually it is recommended that wind-permeable barriers such as windbreak material or trees are used for stock shelter, because solid barriers create turbulence on the leeward side (Gregory 1995). However, ewes and lambs prefer barriers with low wind permeability (Winfield et al 1969;Lynch & Alexander 1977;Alexander et al 1979;.…”
Section: Effective Design and Location Of Sheltermentioning
confidence: 99%
“…In both studies a higher incidence of internal parasitism was observed in the sheltered groups. Other health problems may be associated with shelter, such as footrot, Clostridia infections and facial eczema (Gregory 1995).…”
Section: Effects Of Shelter On Productivity and Healthmentioning
confidence: 99%
“…The lower critical temperature for a dairy cow in peak lactation is around -30°c in dry, still conditions (Blaxter 1958;young 1981;Gregory 1995). These lower critical temperatures may be more relevant for Northern Hemisphere environments where housing is common, thereby limiting exposure to wind or rain.…”
Section: Introductionmentioning
confidence: 99%
“…The higher forage production in May and November is due to greater plant development in these periods, which are periods close to the rainy season, compared to forage production in the middle of the drought period of July. This also explains the smaller forage height in July and taller height in November (Table 5).Trees contribute to the conservation of soil cooling and moisture, by protecting the area from direct sun light and winds that sweep the humid air (Gregory, 1995). Thus, the SSP increases absorption of nutrients by forage, resulting in a higher content of biomass and improving the bromatological quality of pastures.…”
Section: Leaf Area Indexmentioning
confidence: 93%